Mild traumatic brain injury in children: Management practices in the acute care setting. (16th June 2014) - Kool, Bridget; King, Vivienne; Chelimo, Carol; Dalziel, Stuart; Shepherd, Michael; Neutze, Jocelyn; Chambers, Nikki; Wells, Susan
Abstract Objective Accurate diagnosis, treatment and follow up of children suffering mild traumatic brain injury (MTBI) is important as post‐concussive symptoms and long‐term disability might occur. This research explored the decisions clinicians make in their assessment and management of children with MTBI in acute care settings, and identified barriers and enablers to the delivery of best‐practice care. Methods A purposeful sample of 29 clinicians employed in two metropolitan paediatric EDs and one Urgent Care clinic was surveyed using a vignette‐based questionnaire that also included domains of guideline awareness, attitudes to MTBI care, use of clinical decision support systems, and knowledge and skills for practising evidence‐based healthcare. Results Overall, the evaluation and management of children presenting acutely with MTBI generally followed best‐practice guidelines, particularly in relation to identifying intracranial injuries that might require surgical intervention, observation for potential deterioration, adequate pain management and the provision of written head injury advice on discharge. Larger variation emerged in regard to follow‐up care and referral pathways. Potential barriers to best‐ practice were lack of guideline awareness, attitudes to MTBI, and lack of time or other priorities. Conclusions Opportunities exist to improve care for children who present in acute care settings following mild traumatic brain injury. These include having up‐to‐date guidelines that are consistent across acute care settings; providing clearer pathways for referral and follow up; targeting continuing medical education towards potential complications; and providing computerised decision support so that assessment and management are conducted systematically.